Combining cosmetic injectables with low‐energy, low‐density 1927 nm fractional thulium fiber laser: A 2.5‐year examination on the safety of same‐day treatments. (25th March 2021) - Wang, Jordan V.; Akintilo, Lisa; Geronemus, Roy G.
Abstract: Combining laser treatments with cosmetic injectables can offer synergistic benefit, increased convenience for both patients and physicians, and lessened overall patient downtime. Although paired treatments can be effective, there remain theoretical concerns that this may add new risks. Theoretical risks of combining laser treatment with neurotoxin injections include unintentional spread of the neurotoxin, which may result in eyelid ptosis and muscle weakness. Potential risks with soft‐tissue fillers include unexpected loss of filler volume, necrosis, burn, and product migration. This retrospective chart review of single‐session, same‐day facial treatments using a low‐energy, low‐density 1927 nm fractional thulium fiber laser and cosmetic injectables found no adverse events related to this combination approach. This is important safety information that can offer reassurance to physicians using this clinical approach.